Are adherence to the Mediterranean diet and siesta individually or jointly associated with blood pressure in Spanish adolescents? Results from the EHDLA study - Arthur Eumann Mesas; Arthur Eumann Mesas; Estela Jimenez-López; Estela Jimenez-López; Estela Jimenez-López; Vicente Martínez-Vizcaíno; Vicente Martínez-Vizcaíno; Rubén Fernández-Rodríguez; Bruno Bizzozero-Peroni; Bruno Bizzozero-Peroni; Miriam Garrido-Miguel; Miriam Garrido-Miguel; et al. (Frontiers Media S.A., 2022)
BackgroundBoth dietary and sleep patterns can influence both blood pressure levels and heart rate, but these associations have been understudied in adolescents. Furthermore, it is not known whether diet and sleep could exert a synergistic effect with respect to the maintenance of optimal BP levels in this population.ObjectiveTo investigate the relationship of blood pressure levels with the combination of higher adherence to the Mediterranean diet and the habit of siesta (daytime napping) in Spanish adolescents.MethodsA cross-sectional study was conducted with data obtained through personal interviews and physical examination from a representative sample of 1,378 adolescents (12-17 years of age) from the Valle de Ricote (Region of Murcia, Spain) selected using a simple random sampling technique. Adherence to the Mediterranean diet was assessed with the Mediterranean Diet Quality Index in Children and Adolescents, and the frequency and duration of siesta were self-reported. Objective measurements of systolic and diastolic blood pressure were obtained under standardized conditions. Statistical procedures were performed with SPSS software (v.25) and included logistic and generalized regression models adjusted for sex, age, socioeconomic status, body mass index, total energy intake, nighttime sleep duration, and moderate-to-vigorous physical activity.ResultsOf the 698 adolescents finally studied (mean age 13.9 ± 1.5 years; 56.2% female), 37.1% (n = 259) had high adherence to the Mediterranean diet and 19.6% (n = 137) reported frequent siesta. In the completely adjusted models, compared to adolescents with low Mediterranean diet adherence and no or infrequent siesta, those with high Mediterranean diet adherence and frequent siesta were less likely to have high-normal blood pressure or hypertension (odds ratio = 0.47; 95% confidence interval: 0.26, 0.88) and showed slightly lower systolic blood pressure (ß-coef. = −2.60; 95% CI: −5.18, −0.02).ConclusionGreater adherence to the Mediterranean diet and frequent siesta have a synergistic effect on maintaining lower blood pressure levels in adolescence. These findings reinforce that adherence to both Mediterranean lifestyle behaviors early in life may be an important strategy to prevent hypertension throughout adulthood.